(untitled) (Fiep Bulletin - online, 2015)
Education appears to be on the fringes of a series of revolutionary changes in methodology. These chances involve the application of recent advances in technology to teaching. It would appear that methods of education which have remained relatively unchanged, will be changed in a starling way. These changes may reverberate throughout the entire educational structure causing changes in the training of teachers, in the organization of the curriculum, lesson planning, methods of teaching, school buildings, the selection of children for various types of education, etc.